2019
DOI: 10.1093/jas/skz109
|View full text |Cite
|
Sign up to set email alerts
|

Forms of selenium in vitamin-mineral mixes differentially affect serum alkaline phosphatase activity, and serum albumin and blood urea nitrogen concentrations, of steers grazing endophyte-infected tall fescue

Abstract: The goal of this study was to test the hypothesis that sodium selenite (ISe), SEL-PLEX (OSe), vs. a 1:1 blend (MIX) of ISe and OSe in a basal vitamin-mineral mix would differentially affect serological and hepatic parameters of growing steers grazing toxic endophyte-infected tall fescue-mixed forage pasture. Predominately Angus steers (BW = 183 ± 34 kg) were randomly selected from herds of fall-calving cows grazing endophyte-infected tall fescue-mixed pasture and consuming vitamin-mineral mixes that contained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 44 publications
(67 reference statements)
3
4
1
Order By: Relevance
“…In a previous study, growing steers that grazed on HE of a similar concentration of ergovaline and ergovalinine (0.52 ppm) and consumed a vitamin-mineral mix that contained ISe as the form of supplemental Se developed symptoms of fescue toxicosis, including reductions in their serum prolactin concentrations and levels of alkaline phosphatase activity (Brown et al, 2009;Jackson et al, 2015). Similarly, we also observed reductions in the serum prolactin concentrations and serum alkaline phosphatase activity levels of the ISe-treatment steers in the present study (Jia et al, 2019). In addition, we reported previously that the hepatic alkaline phosphatase content observed in the ISe steers in the present study was lower than that observed in the MIX and OSe steers (Jia et al, 2019).…”
Section: Animal Modelsupporting
confidence: 85%
“…In a previous study, growing steers that grazed on HE of a similar concentration of ergovaline and ergovalinine (0.52 ppm) and consumed a vitamin-mineral mix that contained ISe as the form of supplemental Se developed symptoms of fescue toxicosis, including reductions in their serum prolactin concentrations and levels of alkaline phosphatase activity (Brown et al, 2009;Jackson et al, 2015). Similarly, we also observed reductions in the serum prolactin concentrations and serum alkaline phosphatase activity levels of the ISe-treatment steers in the present study (Jia et al, 2019). In addition, we reported previously that the hepatic alkaline phosphatase content observed in the ISe steers in the present study was lower than that observed in the MIX and OSe steers (Jia et al, 2019).…”
Section: Animal Modelsupporting
confidence: 85%
“…The change in selenoprotein gene expression by the liver indicates that MIX steers have a greater redox signaling capacity and capacity to manage oxidative damage than ISe steers. We conclude that inclusion of 3 mg Se/d OSe or MIX forms of Se in free-choice vitamin-mineral mixes alters the selenoprotein transcriptome of both the pituitary and liver of growing steers consuming a Sedeficient (0.07 ppm) endophyte-infected tall fescue forage, in an ostensibly positive manner, consistent with the Se treatmentspecific amelioration of important markers of fescue toxicosis in these same steers (Jia et al, 2018;Li et al, 2019;Jia et al, 2019).…”
Section: Discussionsupporting
confidence: 67%
“…To date, our research has shown that the form (inorganic, organic, 1:1 mix of inorganic:organic) of supplemental (3 mg/d) dietary Se affects the concentration of Se in whole blood and expression of certain genes in the testes of neonatal calves (Cerny et al, 2016), livers of replacement beef heifers (Matthews et al, 2014), and livers (Jia et al, 2018) and pituitaries (Li et al, 2019) of growing beef steers. Most recently, we have reported (Jia et al, 2018;Jia et al, 2019) that the whole blood concentration of Se in Study 2 steers was greater for OSe (11%) and MIX (7.5%) vs. ISe steers, indicating a greater whole-body Se assimilation for OSe and MIX steers. In addition, the OSe and MIX steers of Study 2 had greater concentrations of serum prolactin and albumin (Jia et al, 2018), and serum alkaline phosphatase activity (Jia et al, 2019) than ISe steers, and were positively correlated with whole blood Se concentrations.…”
Section: Physiological Consequence Of Se Forminduced Alteration Of Se...mentioning
confidence: 80%
See 1 more Smart Citation
“…To further complicate the interpretation of the urea data, an increase in blood urea concentration in Se supplemented animals was also observed in rats supplemented with inorganic Se [48] and in one year old Angus steers fed organic Se [49] but not in multiparous dairy cows [41,50]. Thus, it is possible that the observed increased circulating urea by feeding Se-bioforti ed hay might only be associated with the young age of the cows used.…”
Section: Selenium Bioforti Ed Hay Improves Albumin Production By the mentioning
confidence: 99%